(3GdYbhHGJ GdGbJUGOjI GdOhdjI (B:s (3aj GdbGfhf GdOhdj Hjf GdaYGdjI h Mbhb GdGfSGf (B/s - (3CHj Ndjd, QhOQjc GjdjGs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2009)
(3JWhQ eaghe GdGef GdGfSGfj cfXQjI eYjGQjI , eGHjf GdJfejI h GdGef GdGfSGfj , GdYbhHGJ cLRGA aj GdYdGbGJ GdOhdjI , fLGM GdYbhHGJ Hjf eYGjjQ GdbjGS h GdVhGHW GdGNdGbjI , GdYQGb eGHjf GdbQGQGJ GdOhdjI h GdefCSGI GdjhejI , GdYbhHGJ GdGbJUGOjI bhVJ GdfXde GdYQGbj Ce bhJg (B.s
(3eQGLY U(B.205 (3; edGMb U(B.219s
Keywords: (3GdGbJUGO GdOhdjs; (3GdYbhHGJs; (3GdbGfhf GdOhdjs; (3Mbhb GdEfSGfs